Eksekusi Jaminan Hak Tanggungan Berdasarkan Putusan Pengadilan Yang Bersifat Condemnatoir (Studi Kasus Putusan Nomor 76/PDT.G/2010/PN.Suoharjo) - Kusuma, Mohammad Harisma Dyah, Shalman Al Farizi, S.H., M.Kn, Septarina Budiwati, S.H., M.H (2016)
This study aims to investigate the implementation and consideration of the judge in the Execution Guarantee Mortgage Based Characteristically condemnatoir Court decision (Case Study Decision No. 76/Pdt.G/2010/Pn.Sukoharjo). Testament accounts payable often found in cases of breach of contract between the plaintiff and the defendant are ultimately resolved by collateral such as land and buildings, it is concluded the defendant filed a lawsuit in default. Asking the auction execution, change their losses due to breach of contract agreement between creditors and debtors. The provisions in Chapter II and Chapter III applies to the engagement arising from a contractual associated with the power of nature condemnatoir encumbrance of an agreement. In principle, it is, because of default usually leads to demands for compensation, expressed in a certain amount of money. Basing on the legal provisions applicable settlement of bad debts on behalf of Plaintiffs do Parate Execution. The first defendant is entitled to sell the Object disputes pursuant to Article 6 in conjunction with Article 20, paragraph 1 of Law No. 4 1996 About Mortgage contained in the Deed Granting Mortgage.